Screening for Potential Compounds using Drug-Repurposing and Virtual Screening of N-Methyl-S-Aspartate (NMDA) Receptor for Autism Spectrum Disorder (ASD) - Nordina Syamira Mahamad Shabudin,; Ahmad Naqib Shuid, (Tropical Life Sciences Research, 2025)
In Malaysia, the study on autism spectrum disorders (ASD) is limited. Most studies only focus on gene neuroligin 3 (NLGN3), NLGN4X, neurexin 1 (NRXN1) and SH3. This study focuses on the N-methyl-D-aspartate (NMDA) that was believed to have a significant effect on ASD. In this study, potential compounds and drugs that can restore receptor function in autistic patients were analysed. This research used an effective in silico method known as drug-repurposing to discover and rediscover drugs and analyse the binding of potential compounds or drugs to the NMDA receptor. AMPA and DOCK4 were used as controls in this study. Using a trusted server, Drug ReposER, 13 potential compounds or drugs that bind to NMDAR were identified. Then, proceed to the docking of potential compounds or drugs that bind to the NMDA receptor using Autodock Vina, Autodock, Hdock and CB dock and three drugs were selected that have the best binding score to NMDA, AMPA and DOCK4. The drugs were alitretinoin, salicylic acid and indinavir, respectively. Next, molecular dynamics simulations were performed with all selected compounds to study drug-protein binding, with detailed analysis of bond stability using root-mean-square fluctuation (RMSF) oscillations. Finally, ADMET (Absorption, Distribution, Metabolism, Excretion and Toxicity) predictions identify 4-androstenedione, tryptophan, carbocisteine and vitamin A as having minimal toxic effects. This study showed that alitretinoin, which was known to treat skin lesions from Kaposi’s sarcoma, might have the ability to reverse the effect in ASD, particularly in NMDA receptors, potentially making a significant impact on the field of neurology and psychiatry.